Superoxide Dismutase Mimic, MnTE-2-PyP Enhances Rectal Anastomotic Strength in Rats after Preoperative Chemoradiotherapy. (14th April 2020) - Yang, Yu; Wang, Qi; Luo, Jiajun; Jiang, Yue; Zhou, Rui; Tong, Shilun; Wang, Zhihua; Tong, Qiang
Abstract : Background . Rectal cancer is one of the malignant diseases with high morbidity and mortality in the world. Currently, surgical resection is the main treatment method, and preoperative chemoradiotherapy (CRT) is widely used in clinical application to increase resectability and decrease the local recurrence rate. However, CRT increases the risk of colon anastomotic leak, and currently, there are no FDA approved treatments against this side effect. It is essential to develop new drugs to reduce postoperative anastomotic leak after preoperative CRT. Methods . 90 rats underwent standard resection and intestine anastomosis treatment and were divided into six groups for different treatments. During the relaparotomy, bursting pressure of anastomosis was measured and intestinal segments were taken for histopathologic examination and biochemical analyses. RT-PCR and ELISA were applied to measure matrix metalloproteinase (MMP) mRNA and protein levels. Blood vessels were observed by immunohistochemistry, and collagen deposition was observed by Picrosirius Red staining. Results . Preoperative CRT reduced the postoperative anastomotic strength. MnTE-2-PyP increased the bursting pressure and hydroxyproline levels of intestine anastomosis after CRT treatment. Mechanically, MnTE-2-PyP decreased the MMP levels and increased microvessel density (MVD) and collagen deposition. The MMP inhibitor doxycycline had a positive effect on anastomosis healing, but was inferior to MnTE-2-PyP. Conclusions . MnTE-2-PyP enhanced intestine anastomotic strength in rats with preoperative CRT. Specifically, MnTE-2-PyP decreased MMP levels and increased MVD in anastomosis. Therefore, MnTE-2-PyP may be helpful in the prevention of anastomotic leak after preoperative CRT.